Audio Hypno-Analgesia Intervention Effect On Pain Levels During Wound Treatment At JR Care Nursing Practice - Hanung Prasetya; Heryyanoor Heryyanoor; Annisa Febriana ((JKG) Jurnal Keperawatan Global, 2021)
Background: Wound care often causes complaints of side effects, pain, and discomfort for patients, which need to be minimized. Efforts to minimize pain and discomfort include the provision of hypnoanalgesia complementary therapy interventions with additional hypnosis audio hypnoanalgesia methods that cause a feeling of relaxation in patients during wound care. This study analyzed the effect of audio hypnoanalgesia on pain levels in wound care. Methods: Quasi-experimental research using a random control trial was conducted at the JR Care Independent Nursing Practice, Banjarbaru from January to December 2020. The population was 120 patients with total randomization of 60 subjects from the treatment group and 60 subjects from the control group receiving standard care. The independent variable is audio hypnoanalgesia, while the dependent variable is the level of pain. Hypnoanalgesia was performed using hypnosis recordings/audio while pain level was measured using a numerical pain scale of 0 to 10. Data analysis used an independent t-test. The effect of the treatment was seen from the difference in the level of pain before and after being given treatment. Result: Subjects experienced a significant decrease in mean pain in the treatment group from a mean of 4.95, SD = 0.67 before treatment to a mean of 0.13, SD = 0.34 after treatment, effect size 0.97 using Cohen's formula and statistically significant (p = 0.000) which means the administration of audiohypnoanalgesia has a positive effect on reducing pain levels. Conclusion: Hypnoanalgesia audio therapy can be used to minimize patient pain during wound care.